Formulation and Characteristics of Red Palm Oil Nanostractured Lipid Carriers Prepared by Microemulsion Method and Its Application in Drinking Yoghurt - Dahlia Elianarni; Sri Raharjo; Supriyadi Supriyadi (Indonesian Association of Food Technologists, 2022)
The aim of this study was to investigate the characteristic of red palm oil nanostructured lipid carriers (RPO-NLC) made with microemulsion method. The microemulsion procedures prepared with ratio Tween 80 : Span 20 (80:20 ; 70:30), lipid : surfactant (1:3.75 ; 1:4), red palm oil : palm stearin (8:2 ; 7:3 ; 6:4). The best particle size was found at ratio 80:20, 1:4, 6:4 respectively with 24.73 ± 0.06 nm, zeta potential -7.43, turbidity 0,183% and polydispersity index at 0.06. This formulation indicated a loading capacity of 1.97%, encapsulation efficiency of 99.57%, FTIR, DSC, and stable emulsion at room temperature storage for four weeks. This best formulation was applied in drinking yoghurt with ratio nanostructured lipid carrier and yoghurt 1:18. The pH of yoghurt drink containing RPO-NLC increased from 4.13 to 4.37, while its encapsulation stability decreased from 78.45% to 49.29%. The results of sensory evaluation showed no significant difference in color, aroma, but there was significant difference on the taste of drinking yoghurt.